IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM KURIKULUM 2013 PADA SISWA KELAS II SDN 111 PEKANBARU - Andriani, Silvina; Kurniaman, Otang; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to describe the planning , implementation of learning and obstacles encountered by the teachers and the efforts to overcome obstacles in the implementation of Scientific Approach in class II SDN 111 Pekanbaru. This research is qualitative . The subjects were second grade teacher , second grade students, and the head of the SDN 111 Pekanbaru. The object of this research are activities which are a form of implementation of the Scientific Approach . Instruments in this study are guidelines for observation , interview , questionnaire sheet , and guidelines RPP analysis. Data were analyzed using data reduction , data display , and conclusion. Test the validity of the data using triangulation techniques and resources . The results showed that teachers do lesson planning is reviewing the syllabus and teacher books , and to develop lesson plans that outline measures Scientific Approach activities. Teachers are already implementing learning using Scientific Approach activities include observing , ask , gather information / try , associate / reasoning , and communicate , it is in conformity with Permendikbud No. 103 of 2014 on Education in Basic Education. However , the closing is done by the class teacher at SDN 111 II Pekanbaru still less appropriate to permendikbud No. 103 in 2014 because there are some activities that are not carried out by the class teacher II. Barriers experienced teachers in the implementation of scientific approaches include barriers in the planning and implementation of learning.Key words : implementation , scientific approach , curriculum 2013